Regretting your occupation constructively: a qualitative study of career choice and occupational regret - Budjanovcanin, Alexandra [Verfasser]; Woodrow, Chris [Verfasser] (My University, 2022)
“Regret is a universal emotion that can be experienced throughout the course of life, with varying degrees of consequence. However, studies have rarely explored regret as it pertains to one's occupational choice. Through an inductive qualitative study drawing on 51 career-based interviews, we develop a model of occupational regret that reveals how individuals experience and deal with this emotion over time. This model shows that the experience of occupational regret is episodic in nature, involves cycles, and manifests differently dependent upon the path taken through episodes. Five different pathways through regret episodes emerged from our analysis, each leading to a distinct regret profile. These profiles are termed Early Responders, Explorers, Stagnaters, Reconciled Acceptors, and Crystallisers. The findings expand our knowledge of domain specific regret and facilitate the identification of possible strategies to constructively navigate this emotion.” (authors’ abstract; BIBB-Doku)

Die Studie untersucht die Erfahrung des Bedauerns beruflicher Entscheidungen. Unterschieden werden hierbei fünf Profile, wie Zeiten des Bedauerns durchlaufen und erlebt werden. So leben beispielsweise "Stagnaters" über Jahre mit ihrem Bedauern und versuchen, lediglich die Auswirkungen des Bedauerns zu mildern – ohne eine Ursachenbekämpfung. Demgegenüber reagieren "Early Responders" effektiv auf die ersten Auslöser des Bedauerns und handeln aktiv, bevor es zu wiederholten Zyklen des Bedauerns kommt. Die Studie identifiziert abschließend Strategien zum konstruktiven Umgang mit dem Bedauern beruflicher Entscheidungen. (BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2 Übergänge; 370; 300; Berufsentscheidung; Berufswahlverhalten; Emotionale Disposition; Modellierung; Typologie